Decreased TNF Levels and Improved Retinal Ganglion Cell Survival in MMP-2 Null Mice Suggest a Role for MMP-2 as TNF Sheddase. (15th September 2015) - De Groef, Lies; Salinas-Navarro, Manuel; Van Imschoot, Griet; Libert, Claude; Vandenbroucke, Roosmarijn E.; Moons, Lieve
Abstract : Matrix metalloproteinases (MMPs) have been designated as both friend and foe in the central nervous system (CNS): while being involved in many neurodegenerative and neuroinflammatory diseases, their actions appear to be indispensable to a healthy CNS. Pathological conditions in the CNS are therefore often related to imbalanced MMP activities and disturbances of the complex MMP-dependent protease network. Likewise, in the retina, various studies in animal models and human patients suggested MMPs to be involved in glaucoma. In this study, we sought to determine the spatiotemporal expression profile of MMP-2 in the excitotoxic retina and to unravel its role during glaucoma pathogenesis. We reveal that intravitreal NMDA injection induces MMP-2 expression to be upregulated in the Müller glia. Moreover, MMP-2 null mice display attenuated retinal ganglion cell death upon excitotoxic insult to the retina, which is accompanied by normal glial reactivity, yet reduced TNF levels. Hence, we propose a novel in vivo function for MMP-2, as an activating sheddase of tumor necrosis factor (TNF). Given the pivotal role of TNF as a proinflammatory cytokine and neurodegeneration-exacerbating mediator, these findings generate important novel insights into the pathological processes contributing to glaucomatous neurodegeneration and into the interplay of neuroinflammation and neurodegeneration in the CNS.